New Steroidal Erythrityl Triesters from the Heat Processed Roots of Panax ginseng - Ill-Min Chung; Mohd Ali; Ye-Seul Yang; Jae-Yeon Yoon; Youn-Pyo Hong; Ateeque Ahmad (Journal of Chemistry)
Two new compounds stigmasta-3α-ol-3α-(2′R,3′S)-butane-1′,2′,3′,4′-tetraolyl-2′,3′-dioctadec-9″/9‴-enoyl-4′-octadec-9″″,12″″-dienoate (1) and stigmasta-5-en-3β-ol-3β-(2′R,3′S)-butane-1′,2′,3′,4′-tetraolyl-2′,3′-dioctadec-9″/9‴-enoyl-4′-octadec-9″″,12″″-dienoate (2) along with β-sitosterol-β-D-glucoside were isolated and identified from the heat processed roots of Panax ginseng. The structures of the new compounds were elucidated by 1D and 2D NMR (COSY, HSQC, and HMBC) spectroscopic techniques aided by FAB-MS, ESI FT/MS, and IR spectra.